The role of school leadership in improving international test results (TIMSS) from the point of view of teachers in Taif - Al-Osimi, Ahmed Mohammed Hamdan (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the role of school leadership in improving the results of international tests (TIMSS) from the point of view of teachers in the city of Taif. The study used the descriptive analytical method and a questionnaire of (35) phrases divided into five dimensions, which were applied to a sample of (643) male and female teachers in the city of Taif. This sample obtained a total mean of (2.51) out of 5, which is a small degree. And it became clear from the results that the role of the reality of school leadership in improving the results of international tests TIMSS was represented in the dimension of school organization and coordination. Where it came in the first place with an average of (2.70) and a medium degree of appreciation, followed by the sponsorship of students with an average of (2.62) and a medium degree of appreciation. While it came after leadership style and educational supervision in the third place with an average of (2.51) and a low degree of appreciation. After the professional development of teachers, it came in fourth place, with an average of (2.40) and a low degree of appreciation. Finally, it came after the school environment and the organizational climate, with an average of (2.35), and a little estimate. The results also showed that there were no statistically significant differences at the level of (0.05) or less about the reality of the role of school leadership in improving the results of the TIMSS international tests, due to study variables such as gender, years of experience and the number of training courses. Based on the results, the researcher presented a number of recommendations and suggestions. Among these recommendations and suggestions are urging school leaders to plan school to improve the educational attainment of students and work to reduce the assignment of outstanding mathematics and science teachers in administrative work. Among these recommendations and suggestions is also an interest in enhancing teachers' familiarity with the international test standards TIMSS, as well as making complementary studies on the subject.
Keywords: school organization and coordination; student care; educational leadership and supervision; professional development for teachers; school environment and organizational climate